2020
DOI: 10.1116/6.0000381
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cryo-processing on the mechanical and biological properties of poly(vinyl alcohol)-gelatin theta-gels

Abstract: Poly(vinyl alcohol) (PVA), a synthetic, nontoxic polymer, is widely studied for use as a biomedical hydrogel due to its structural and physicomechanical properties. Depending on the synthesis method, PVA hydrogels can exhibit a range of selected characteristics-strength, creep resistance, energy dissipation, degree of crystallinity, and porosity. While the structural integrity and behavior of the hydrogel can be finetuned, common processing techniques result in a brittle, linear elastic material. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…These composites can be used as scaffolds for cell cultures. [ 23,25,26 ] As the most abundant protein in mammal bodies, collagen (COL) is an ideal raw material for the tissue healing process due to good biocompatibility, biodegradability, and inductivity for cell proliferation. [ 27 ] However, it is difficult for COL to display its bioactivity due to degradation continuously.…”
Section: Introductionmentioning
confidence: 99%
“…These composites can be used as scaffolds for cell cultures. [ 23,25,26 ] As the most abundant protein in mammal bodies, collagen (COL) is an ideal raw material for the tissue healing process due to good biocompatibility, biodegradability, and inductivity for cell proliferation. [ 27 ] However, it is difficult for COL to display its bioactivity due to degradation continuously.…”
Section: Introductionmentioning
confidence: 99%
“…Pterostilbeneloaded PVA/Gel cryogels have been reported as a potential dressing material in wound therapy, promoting cell viability and proliferation. [48][49][50] However, it has been reported that PVA/Gel cryogel promotes the viability and proliferation of endothelial cells and is particularly suitable for vascular tissue engineering applications. [50] In addition, it was determined that there was no cytotoxic effect for human skin cells cultured in PVA/Gelatin cryogel and the scaffold exhibited good biocompatibility.…”
Section: Assessment Of Cell Viability Of Cryogels By Mtt Assay Trypan...mentioning
confidence: 99%
“…For these reasons, it has been reported to be a promising platform in tissue engineering. Pterostilbene-loaded PVA/Gel cryogels have been reported as a potential dressing material in wound therapy, promoting cell viability and proliferation [57][58][59]. However, it has been reported that PVA/Gel cryogel promotes the viability and proliferation of endothelial cells and is particularly suitable for vascular tissue engineering applications [59].…”
Section: Assessment Of Cell Viability Of Cryogels By Mtt Assay Trypan...mentioning
confidence: 99%